Milne's equation for polarized light and a related Markov process - Waldenfels, Wilhelm von (Stochastics, 2009)
Starting from the radiative transfer equation for polarized light formulated with the help of the intensity tensor we introduce the mean intensity tensor. We derive the analogue of Milne's integral equation and interpret that equation as the potential equation of a Markov process.